Knowledge, Attitude And Practice Of Medical Practitioners Regarding Breastfeeding: A study at a Tertiary Care Hospital of Karachi - Shaista Ehsan; Uzma Ghori; Farah Agha (ziauddin University, 2024)
Background: Physicians play a crucial role in the promotion and support of breastfeeding. Although many studies have been conducted to evaluate the knowledge about breastfeeding in mothers, few studies are found in literature discussing the knowledge and practice of physicians regarding breastfeeding .To assess the knowledge, attitude and practice of medical practitioners about breastfeeding at a tertiary care hospital. Methods: A cross-sectional study was conducted on 200 physicians of Ziauddin University belonging to the specialties of Pediatrics, Gynecology/Obstetrics, General Medicine and Family Medicine. The participants filled a structured questionnaire after informed consent. Data was analyzed on SPSS 20.0. Categorical variables were expressed as frequencies and percentages while continuous variables were presented as mean. P value of <0.05 was considered significant. Results: A total of 200 medical practitioners participated in the study. 97% of the respondents recommended exclusive breastfeeding for the first six months of life. Formula feeding was also considered equally acceptable by 66.5%. Pre-lacteal feeds were forbidden by 74% and 82% of the participants had not attended any Continuing Medical Education (CME) program on breastfeeding in the last 03 years. Conclusion: The shortcomings in the breastfeeding counseling skills of physicians and in their ability to manage lactational problems need to be addressed. A written hospital policy on breastfeeding is mandatory. Key Words: Breastfeeding, Lactation, Attitude, Practice, Pre-lacteal.